Lowering the bar of high-sensitivity cardiac troponin: more than limbo dancing? - Haaf, Philip (Journal of Laboratory and Precision Medicine; Vol 2 (August 2017): Journal of Laboratory and Precision Medicine, 2017)
To discharge or not to discharge remains one of the most common and contentious questions emergency department (ED) physicians are confronted with in patients presenting with acute chest pain. The success story of contemporary high-sensitivity cardiac troponin (hs-cTn) assays is remarkable and had great impact on this question: Biomarkers for the diagnosis of acute myocardial infarction (AMI) were first introduced in the 1960s with the use of aspartate transaminase (AST) which was also incorporated into the World Health organization (WHO) definition of AMI (1,2).